Answer:
฿₹Ø: 1391 US$
Step-by-step explanation:
Answer:
hence cos ( 2 A ) = cos 2 A − ( 1 − cos 2 A ) = 2 cos 2 A − 1
Step-by-step explanation:Well we know that for two angles A , B
it holds that cos ( A + B ) = cos A cos B − sin A ⋅ sin B hence for A = B you get cos ( 2 A ) = cos 2 A − sin 2 A But sin 2 A = 1 − cos 2 A
Answer:
1(2-3)(4-7)
(1)(-1)(4-7)
-1(4-7)
(-1)(-3)
=3
Step-by-step explanation:
As I can tell the tables are right but it would be a function since none of the x's repeat
Answer: 4 also fish
Step-by-step explanation: